2015
DOI: 10.1186/s12879-015-1136-0
|View full text |Cite
|
Sign up to set email alerts
|

First human case report of sepsis due to infection with Streptococcus suis serotype 31 in Thailand

Abstract: Background: Streptococcus suis is a zoonotic pathogen that causes invasive infections in humans and pigs. It has been reported that S. suis infection in humans is mostly caused by serotype 2. However, human cases caused by other serotypes have rarely been reported. This is the first report of a human case of infection with S. suis serotype 31 in Thailand. Case presentation: A 55-year-old male alcohol misuser with liver cirrhosis was admitted with sepsis to a hospital in the Central Region of Thailand. He had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Human infection caused by S. suis is a rare but lifethreatening condition. Epidemic and sporadic human infection cases caused by S. suis serotype 1, 2, 4, 5, 9, 14, 16, 21, 24 and 31 have also been reported in many countries and 17.8% of patients dead [1,[8][9][10].Timely and accurate diagnosis of pathogenic bacteria is the key to cure. Because of the variable of biochemical characteristics, S. suis is often misidentified as other species of Streptococcus genus [7].…”
Section: Discussionmentioning
confidence: 99%
“…Human infection caused by S. suis is a rare but lifethreatening condition. Epidemic and sporadic human infection cases caused by S. suis serotype 1, 2, 4, 5, 9, 14, 16, 21, 24 and 31 have also been reported in many countries and 17.8% of patients dead [1,[8][9][10].Timely and accurate diagnosis of pathogenic bacteria is the key to cure. Because of the variable of biochemical characteristics, S. suis is often misidentified as other species of Streptococcus genus [7].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 29 serotypes of S. suis are recognized [4]. Of these, serotype 2 is the most prevalent in S. suis human infections, although cases have also been reported caused by serotypes 4,5,9,14,16,21,24, and 31 [1][2][3][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, currently there are 29 true S. suis serotypes. Of them, serotype 2 is the most prevalent in both human and pig infections although cases caused by serotypes 4,5,9,14,16,21,24, and 31 have also been reported [1][2][3][4][14][15][16][17]. A first study reported that a variant of the serum opacity factor (ofs) can serve as a genetic marker to determine CCs of S. suis [39].…”
Section: Introductionmentioning
confidence: 99%